Pronoun “you” in the Functional Aspect - Mykhaylenko, V. V.; Михайленко, В. В. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
The dynamics of the thou-pronoun in ME, its functional paradigm in comparison with OE and NE ones are in the focus of the present research. The issues of the thou-pronoun functional development, its specialization in the religious discourse, and the causes of its shift to the periphery at the end of the ME and the beginning of NE. Статтю присвячено динаміці займен- ника 2-ої особи однини у с.-a. мові порівняно з д.-a. та н.-a. мовою. Розглянуто становлення функціональної па- радигми займенника, його відносну спеціалізацію у релігійному дискурсі та причини периферізації наприкінці с.-а. та початку н.-а. періоду.
Займенник “ти” у функціональному аспекті
Keywords: pronoun; function; discourse; dynamics; periphery; paradigm; addressee; займенник; функція; дискурс; динаміка; периферія; парадигма; адресат